(untitled) (Academicia Globe: Inderscience Research, 2022)
The article deals with the peculiarities of the institute of insignificance of the act in the criminal law of foreign countries. In particular, the review on foreign vision of essence of insignificance of act in the countries of Romano-Germanic and Anglo-Saxon legal families, as well as Muslim law is given.